Association between triglyceride-glucose index and major adverse cardiovascular events in patients with intermediate coronary stenosis: a prospective cohort study - Li, Hui-juan; Zhang, Lei-guang; Xu, Haobo; Wang, Yao-xin; Liu, Shuai; Liu, Jie-yun (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to evaluate the correlation between the triglyceride-glucose (TyG) index and the incidence of major adverse cardiovascular events (MACE) in patients with intermediate coronary stenosis.Methods and resultsA prospective cohort study was conducted involving 217 patients diagnosed with intermediate coronary stenosis confirmed by coronary angiography at Kaifeng Central Hospital. Patients were stratified into quartiles based on the TyG index and were followed for a median period of 858 days. During the follow-up, 35 patients experienced MACE. Kaplan-Meier survival analysis, adjusted for confounding variables in Model 3, demonstrated a significantly elevated risk of MACE in the highest TyG quartile compared with those in the lowest quartile (log-rank p = 0.015). The hazard ratio (HR) for MACE in the highest quartile was 1.87 (95% CI: 1.23–2.18; p = 0.005). Restricted cubic spline analysis demonstrated that the TyG index became a significant risk factor for MACE when exceeding a value of 10.19, with an overall positive trend in risk as the TyG index increased (nonlinear test p = 0.221). Exploratory subgroup analyses indicated that, when assessed as a continuous variable, the TyG index was significantly associated with a higher incidence of MACE among male patients (HR = 1.57; 95% CI: 1.05–2.36; p = 0.047), those aged over 65 years (HR = 1.25; 95% CI: 1.18–3.10; p = 0.027), and those with diabetes mellitus (HR = 1.91; 95% CI: 1.18–3.10; p = 0.021).ConclusionThe TyG index was independently correlated with an increased incidence of MACE in patients with intermediate coronary stenosis. Subgroup analyses indicated that this correlation was particularly pronounced in patients with diabetes mellitus.